2016
DOI: 10.3390/ijms17122031
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Cell Nuclear Transfer Followed by CRIPSR/Cas9 Microinjection Results in Highly Efficient Genome Editing in Cloned Pigs

Abstract: The domestic pig is an ideal “dual purpose” animal model for agricultural and biomedical research. With the availability of genome editing tools such as clustered regularly interspaced short palindromic repeat (CRISPR) and associated nuclease Cas9 (CRISPR/Cas9), it is now possible to perform site-specific alterations with relative ease, and will likely help realize the potential of this valuable model. In this article, we investigated for the first time a combination of somatic cell nuclear transfer (SCNT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Furthermore, GE pigs could be efficiently produced by in vitro EP in the presence of RNP [68]. Sheets et al [82] produced GE fetuses by cytoplasmic MI of RNP into oocytes reconstituted with intact cells using the SCNT technology. By this treatment, they reported highly efficient (100%) generation of bi-allelic modification in the resultant cloned fetuses.…”
Section: History Of Ge In Pigsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, GE pigs could be efficiently produced by in vitro EP in the presence of RNP [68]. Sheets et al [82] produced GE fetuses by cytoplasmic MI of RNP into oocytes reconstituted with intact cells using the SCNT technology. By this treatment, they reported highly efficient (100%) generation of bi-allelic modification in the resultant cloned fetuses.…”
Section: History Of Ge In Pigsmentioning
confidence: 99%
“…For example, in mice, delivering RNPs into zygotes causes rapid genome editing in the target locus, which also maximizes efficiency while minimizing mosaicism [110][111][112]. Indeed, Sheets et al [82] demonstrated that after MI with RNP, 100% of piglets produced had the bi-allelic KO genotype.…”
Section: MImentioning
confidence: 99%
See 1 more Smart Citation
“…Litter sizes and viability are good with this approach, and while early demonstrations had relatively low editing frequency, evolution of the tools and refinement in delivery has resulted in substantive improvements [10,11] . A combination of SCNT followed by zygote microinjection with Cas9 ribonucleoprotein (Cas9 protein pre-complexed with sgRNA) has also been shown to be a very efficient strategy for generation of genome edited pigs [12] .…”
Section: Application In Livestockmentioning
confidence: 99%
“…; Wang, Du, et al., ; Wang, Zhou, et al., ; Whitworth et al., ; Yu et al., ), sheep (Crispo et al., ; Wang, Niu, et al., ; Zhang et al., ), goat (Guo et al., ; Wang, Yu, et al., ) and cattle (Bevacqua et al., ). CRISPR can be also delivered as ribonucleoprotein (Park, Powell, et al., ; Sheets et al., ), with the advantage that it acts faster than RNA delivery, as it does not require the generation of Cas9 protein by the zygote. The components can be also delivered as plasmid (Chuang et al., ; Honda et al., ; Petersen et al., ), but this is the slowest way, as Cas9 needs to be transcribed and translated, and it entails a prolonged presence of CRISPR components that favours the appearance of off‐target effects (OTEs).…”
Section: State Of the Artmentioning
confidence: 99%